THE OR: SMOKING IN A DESIGNATED NON-SMOKING AREA - Taylor, Sue (Operating Room Nurses Association of Canada Journal, 2009)
Has smoking in public places been banned in your province? As of May 31, 2008, most workplaces in Canada were smoke-free. There is now full protection from second-hand smoke in Nunavut, the Northwest Territories, Newfoundland and Labrador, Manitoba, New Brunswick, Ontario, Quebec and Nova Scotia. Meanwhile, in British Columbia, Saskatchewan and Prince Edward Island there are laws providing protection from second-hand smoke for some workers, but not for others, while individuals in the Yukon, Alberta and federal jurisdictions have little or no legal protection from second-hand smoke at work.1